MANAJEMEN MADRASAH BERTARAF INTERNASIONAL AMANATUL UMMAH PACET MOJOKERTO - Intan Budiana Putri; Waslah - (Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2018)
This writing starts from the author's observation of the madrasah which is seen as number two education by the community. This happens because there are still many madrasah that have not carried out management properly. Besides that there are still many madrasah that cannot compete at the regional, national or international levels. Therefore the author tries to do research on one of the madrasah that has managed to do madrasah management well, so that the madrasah can compete at the regional, national and even international levels. The Madrasah is the Amanatul Ummah Pacet International Standard Madrasah Mojokerto. This paper aims to explain the management of the Amanatul Ummah Pacet Mojokerto International Standard Madrasah. This writing uses a qualitative approach, while the type of writing is field writing. This writing is located in the Superior Madrasah Aliyah Amanatul Ummah Surabaya, the program of the Amanatul Ummah International Standard Madrasah in Pacet Mojokerto. In collecting data the author uses interview, observation and documentation methods. In this paper the authors find data on the Management of Amanatul Umah Pacet Mojokerto International Standard Madrasah in terms of management functions which include, planning, organizing, motivation, supervision and evaluation. In addition the authors also found data on supporting factors and inhibiting factors in the management of the Amanatul Umah Pacet Mojokerto International Standard Madrasah and the quality of graduates of the Amanatul Umah Pacet International Standard Madrasah Mojokerto. Keywords: Management, International Standard Madrasah.